2012
DOI: 10.1097/brs.0b013e31824cf756
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Comparison of Nonpenetrating Titanium Clips Versus Conventional Suture for Repair of Spinal Durotomies

Abstract: Nonpenetrating titanium clips provide a durotomy closure with immediate hydrostatic strength similar to intact dura whereas suture repair with either suture was significantly less robust. The use of titanium clips was more rapid than that of suture repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In fact, hydrostatic pressure studies in bovine spines have no difference in CSF leak rates among braided sutures, monofilament sutures, and microclips. 23 Lastly, concerns were initially expressed that the titanium clip artifact may disturb CT or MRI interpretation in the postoperative setting. However, it has been demonstrated that this is not the case on multiple reports.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, hydrostatic pressure studies in bovine spines have no difference in CSF leak rates among braided sutures, monofilament sutures, and microclips. 23 Lastly, concerns were initially expressed that the titanium clip artifact may disturb CT or MRI interpretation in the postoperative setting. However, it has been demonstrated that this is not the case on multiple reports.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] It has demonstrated efficacy for use in major vascular injuries in skull base surgery and has recently been approved for dural reconstruction for its potential in preventing postoperative CSF leaks. 6,35 Thus far, there is evidence that the clips can be used to repair leaks in the spinal dura, [36][37][38][39] as well as one case report that demonstrated the use of titanium clips in repairing a CSF leak at the skull base. 40 Skull base repairs often fail at the leading edge of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Faulkner et al . [3] reported that the dura closure with nonpenetrating titanium clips provides immediate hydrostatic strength similar to intact dura. In conclusion of the previous studies revealed that nonpenetrating titanium clips have the benefits of being technically easy to use, reduced durotomy repair time, decreased bed rest due to related medical complications, superior postoperation with immediate hydrostatic strength, and better reapproximation if it fails to clip successfully.…”
Section: Discussionmentioning
confidence: 99%